Prevalence and Timing of Tracheostomy and Its Impact on Clinical Outcomes in COVID-19 Pneumonia Patients in Dubai Hospital - Rashid Nadeem; Ahmed Najah Zahra; Mustafa Hassan; Yusuf Parvez; Nilesh Gundawar; Mohammed A.M. Hussein; Manal Younis; Manoj P. Mathews; Wasim Khan; Majid Ahmed Saleh; Imran Mumtaz; Hebah Rami Aljaghoub; et al. (Dubai Medical Journal)
Introduction: Coronavirus has caused more than a million deaths as of October 2020. Hospitals consider tracheostomy after the patient is virus negative, usually after 3 weeks. Prevalence and timing of tracheostomy and its impact on survival among COVID patients are unknown. Methods: A retrospective, single-center study of all patients with COVID-19 ARDS who underwent tracheostomy was conducted. Patients with age <18 and patients treated with ECMO were excluded. Duration of ventilation before tracheostomy was recorded. Clinical variables, outcome variables, and confounding variables were recorded and compared between patients with tracheostomy and without tracheostomy. The aim was to determine prevalence and timing of tracheostomy and its impact on clinical outcomes. Results: We found that tracheostomies were performed only in 21 out of 196 patients (10.8%). Tracheostomies were performed after 3 weeks on average (22.1 ± 7.5 days). Survival was significantly higher in patients who underwent tracheostomy (85.7 vs. 42.5%, p = 0.001). LOSICU was longer for tracheostomy patients than patients without tracheostomy (median [IQR]: 35 [23–47] vs. 15 [9–21], p = 0.001). Patients who underwent tracheostomy had a higher proportion of treatment with continuous renal replacement therapy (CRRT) (52 vs. 30%, p = 0.04), more COVID-19 swab testing (6.5 [4.5–8.5] vs. 5 [3–7], p = 0.002), more days on mechanical ventilation (34.5 [24–45] vs. 11 [5.5–16.5], p = 0.001), and more length of stay in the hospital (54 [38–70] vs. 20 [10.5–29.5], p = 0.001). All other factors were not statistically different between the 2 groups. Approximately 29% of patients had possible false-negative testing as their swab became positive after being negative. Conclusion: Tracheostomy was performed only in 10% of our patients with COVID-19 ARDS. Time to tracheostomy was after 3 weeks on average. Survival was better in patients with tracheostomy, but tracheostomized patients stayed longer in the ICU and hospital and utilized more days of mechanical ventilation and CRRT.